EFEKTIVITAS PENDEKATAN DEEP LEARNING PEDAGOGY BERBANTUAN MEDIA INTERAKTIF DIGITAL UNTUK MENINGKATKAN LITERASI MATEMATIKA DAN METAKOGNISI SISWA KELAS VIII DI SMPN 2 BELO - Agustina Agustina; Syarifudin Syarifudin; Taufikurrahman Taufikurrahman; Arif Rahman Hakim; Fatmah Fatmah; Muhammad Fuadi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Low levels of students' mathematical literacy and metacognitive skills remain a major challenge in mathematics learning, particularly in the topic of Systems of Linear Equations in Two Variables (SLETV). Preliminary observations at SMPN 2 Belo revealed that most students experienced difficulties in understanding contextual problems, constructing mathematical models, and reflecting on their thinking processes when solving problems. This study aimed to determine the effectiveness of the Deep Learning Pedagogy approach assisted by interactive digital media in improving the mathematical literacy and metacognitive skills of eighth-grade students at SMPN 2 Belo. This study employed a quantitative method using a quasi-experimental design with a non-equivalent control group design. The population consisted of three eighth-grade classes, while the sample included Class VIII B as the experimental group and Class VIII C as the control group, selected through purposive sampling. The research instruments consisted of a validated mathematical literacy test and a validated metacognitive questionnaire. Data were analyzed using descriptive statistics, N-Gain, normality test, homogeneity test, and the Independent Samples t-Test. The results indicated a significant difference between the experimental and control groups in terms of students' mathematical literacy and metacognitive skills after the intervention. The improvement in both abilities was higher in the experimental group than in the control group. Therefore, the Deep Learning Pedagogy approach assisted by interactive digital media was effective in improving the mathematical literacy and metacognitive skills of eighth-grade students at SMPN 2 Belo. ABSTRAK Rendahnya kemampuan literasi matematika dan metakognisi siswa masih menjadi permasalahan dalam pembelajaran matematika, khususnya pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Hasil observasi awal di SMPN 2 Belo menunjukkan bahwa sebagian besar siswa mengalami kesulitan memahami masalah kontekstual, membangun model matematika, serta merefleksikan proses berpikir dalam menyelesaikan masalah. Penelitian ini bertujuan mengetahui efektivitas penerapan pendekatan Deep Learning Pedagogy berbantuan media interaktif digital untuk meningkatkan literasi matematika dan metakognisi siswa kelas VIII SMPN 2 Belo. Penelitian ini menggunakan metode kuantitatif dengan desain quasi experiment tipe non-equivalent control group design. Populasi penelitian terdiri atas tiga kelas VIII SMPN 2 Belo, sedangkan sampel adalah kelas VIII B sebagai kelas eksperimen dan VIII C sebagai kelas kontrol yang dipilih menggunakan purposive sampling. Instrumen penelitian berupa tes literasi matematika dan angket metakognisi yang telah divalidasi. Analisis data menggunakan statistik deskriptif, N-Gain, uji normalitas, uji homogenitas, dan Independent Samples t-Test. Hasil penelitian menunjukkan terdapat perbedaan signifikan antara kelas eksperimen dan kelas kontrol pada kemampuan literasi matematika dan metakognisi setelah perlakuan. Peningkatan kedua kemampuan pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Dengan demikian, pendekatan Deep Learning Pedagogy berbantuan media interaktif digital efektif meningkatkan literasi matematika dan metakognisi siswa kelas VIII SMPN 2 Belo.